PENGARUH KEBUTUHAN INSENTIF DAN MOTIVASI BERPRESTASI TERHADAP KEPUASAN GURU DI SD IQRA’ TUAH SAKATO MUARA BULIAN - Devita Hardivia Angel; Amiruddin; Zilawati; Muhammad Yusup; Fitri Nasution (PT. Hasba Edukasi Mandiri, 2025)
This research aims to analyze the influence of the need for incentives and achievement motivation on the job satisfaction of teachers at SD IQRA’ Tuah Sakato Muara Bulian. The background of this research is based on the importance of internal and external factors in enhancing the performance and satisfaction of educators. A quantitative method is used, with data collection conducted through surveys by distributing questionnaires to all teachers at the school. The data is processed using multiple regression analysis to identify the effect of each independent variable on the dependent variable. The findings of the study reveal that both the need for incentives and achievement motivation have a positive and significant effect on teachers' job satisfaction. This finding indicates that providing appropriate incentives and encouragement to excel can enhance teachers' satisfaction in performing their duties and responsibilities. This research is expected to serve as a guideline for the school in designing policies that support the welfare and motivation of teachers sustainably.